2023
DOI: 10.1371/journal.pclm.0000065
|View full text |Cite
|
Sign up to set email alerts
|

Public opinion on climate change in China—Evidence from two national surveys

Abstract: China’s ambitious initiatives to address climate change have attracted significant scholarly attention, yet much less focus was on how climate change is understood in Chinese society. This study analyzes the results from two surveys in 2009 and 2016 with nationally representative samples. The findings suggest that Chinese people have a fairly high awareness of the existence and anthropogenic causes of climate change. They consider climate change less urgent than air pollutions but more important than conservat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Several studies have used correlation analysis to investigate the relationship between public opinion and different factors such as demographic, socio-economic, and environmental factors (Ge & Lin, 2021;J. C.-E. Liu, 2023;Yu et al, 2013).…”
Section: Researchersmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have used correlation analysis to investigate the relationship between public opinion and different factors such as demographic, socio-economic, and environmental factors (Ge & Lin, 2021;J. C.-E. Liu, 2023;Yu et al, 2013).…”
Section: Researchersmentioning
confidence: 99%
“…Several studies have used correlation analysis to investigate the relationship between public opinion and different factors such as demographic, socio‐economic, and environmental factors (Ge & Lin, 2021; J. C.‐E. Liu, 2023; Yu et al, 2013). In a recently published study, the stakeholders' opinions are integrated with preferences on identified hazards, that is, coastal flooding, water scarcity, and heat stress (Katirtzidou et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“… 108 , 109 In the past ten years, China has experienced a reasonably high level of public knowledge of climate change, and most people acknowledge that the cause is human activity, which is in line with the scientific community. 110 Another recent study concluded that the general attitude towards climate change is evolving in a favorable direction as public understanding of it rises. 111 It is also important to note that Chinese respondents were more concerned about climate change than terrorism, economic progress, or education.…”
Section: Climate Change Adaptation Initiatives In Chinamentioning
confidence: 99%
“…This paper also finds evidence to support previously studied socio-economic trends in American partisan voting behaviors by investigating the effects of its control variables on the constant. This analysis also adds to a growing number of research which utilizes geographic informational systems to analyze the impacts of natural disasters (Holub, 2023;Rudolph, 2017). This paper ends with a discussion on the limits of this analysis and recommendations for other researchers hoping to continue researching related topics.…”
Section: Introductionmentioning
confidence: 99%